Effects of Neoadjuvant Denosumab on Radiological and Histological Responses in Patients Undergoing En Bloc Resection for Giant Cell Tumor of Bone: A Systematic Review - Aditama, Hendra; Pratama, Yo Tendy; S, Dhanan Prastanika; K, Dita Anggara; S, Rhyan Dharma ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: Giant cell tumor of bone (GCTB) is a rare primary bone tumor. The standard treatment is en bloc resection, which can be challenging due to tumor size or location. Denosumab, a monoclonal antibody, has emerged as a promising neoadjuvant therapy for GCTB, potentially facilitating surgical resection. However, its optimal use remains unclear, with debate surrounding its impact on local recurrence. This systematic review aims to synthesize evidence on the histological and radiological changes induced by neoadjuvant denosumab and its impact on surgical outcomes. Methods: This review followed PRISMA guidelines. The medical term "denosumab", "neoadjuvant", "GCTB", "radiological", and "histological" were used in PubMed (423 articles) and Google Scholar (18,100 articles), totaling 18,523 articles to discover studies of the effect of neoadjuvant denosumab on radiological and histological response up to July 2023. Six remaining studies were reviewed and screened for inclusion criteria based on their relevance to the study subject and clinical outcomes. Results: Based on six studies in this review, five showed histological response by decreasing the multinucleated giant cells and osteoclasts after neoadjuvant DT. Six studies showed increased significant bone reconstitution as a radiological response in the GCTB locale, replaced the extending tumor into soft tissue by abundant bone production with peripheral shell, and increased ease of en bloc resection. Conclusions: Neoadjuvant denosumab therapy shows promise in managing giant cell tumors of bone (GCTB) by reducing osteoclasts, shrinking tumor volume, and promoting cortical bone formation, thus facilitating en bloc resection. However, further research is needed to confirm these findings.